2009
DOI: 10.1007/s10834-009-9154-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-Employment, Work–Family Fit and Mental Health Among Female Workers

Abstract: Mental health, Self-employment, Work–family fit,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 43 publications
1
18
0
5
Order By: Relevance
“…Voydanoff (2005) found that greater autonomy, more learning opportunities, more workplace respect, more meaningful work, and a supportive workplace culture were associated with increased work to family enrichment. Another study found that increased job satisfaction was associated with greater work to family enrichment for women (Tuttle and Garr 2009).…”
Section: Theoretical Perspective and Previous Researchmentioning
confidence: 98%
“…Voydanoff (2005) found that greater autonomy, more learning opportunities, more workplace respect, more meaningful work, and a supportive workplace culture were associated with increased work to family enrichment. Another study found that increased job satisfaction was associated with greater work to family enrichment for women (Tuttle and Garr 2009).…”
Section: Theoretical Perspective and Previous Researchmentioning
confidence: 98%
“…Table 14 looks at occupational characteristics. Column (1) explores heterogeneity between employed and self-employed workers, since the latter may have different characteristics (e.g., more freedom and control over their job; see, e.g., Dellot, 2014, andTuttle andGarr, 2009) and perform jobs that may be less exposed to foreign competition. Consistent with this intuition, the coefficient on the interaction between IS and the dummy for self-employed workers is negative, albeit imprecisely estimated.…”
Section: Within-industry Heterogeneitymentioning
confidence: 99%
“…Other job resources might work out differently for both employment groups. Regarding social support, research shows that the self-employed report lower levels of social support than employed workers because they lack co-worker support (Taris et al 2008 ; Tuttle and Garr 2009 ), although they can compensate by joining professional networks (Koster and De Vries 2011 ). The self-employed also lack supervisor support, which is negatively related to WFC (Matthews et al 2010 ).…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
“…Among the job demands, long working hours are often mentioned as causing conflict. Working long hours might be incompatible with other life domains and may lead to WFC (Parasuraman and Simmers 2001 ; Tuttle and Garr 2009 ). However, the self-employed report more “passion for work” and higher work engagement (Gorgievski et al 2010 ).…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%